Experimental investigation on heat transfer of n-pentane spray impingement on piston surface - Zhou, Z; Mohd Murad, S; Tian, J; Camm, J; Stone, R (Elsevier, 2018)
Fuel spray impingement on piston surfaces is a concern because it can cause particulate exhaust emissions from gasoline direct injection (GDI) engine. Transient heat transfer plays an important role that directly influences liquid film evaporation and its lifetime. In this paper, the effects of injection temperature, injection pressure, piston temperature and impact distance on n-pentane spray impingement heat transfer were fully examined. Results showed that increasing the piston temperature could increase the rate of heat transfer with a larger surface temperature reduction and a higher heat flux, which led to a shorter liquid film lifetime on the piston surface. Increasing the fuel injection temperature helped to improve atomization of the fuel spray, reduce the penetration distance and mitigate impact, which in turn led to reduced surface cooling and less liquid film on the piston surface. A decrease in impact distance and an increase in injection pressure both caused an increase in surface temperature reduction and heat flux but a decrease in the liquid film residence time. The dimensionless heat flux in terms of Biot and Fourier numbers presented a high similarity during the rapid cooling stage. A dimensionless correlation was formed to quantify this fast time-varying heat transfer behaviour.